International marketing in the Asia-Pacific region. - Chao, Paul, 1919-; Samiee, Saeed; Yip, Leslie Sai-Chung (International marketing review, 2004)
A decision support model is presented and discussed which aims at identifying realistic export opportunities for a given exporting country. The model consists of a screening process of four consecutive filters, through which relevant information on markets (such as country risk indicators, macroeconomic data, imports per product group, etc.) is fed, and which allows the identification and deletion of less interesting market opportunities. Results are reported of the application of this decision support model to the case of Thailand, adapted for an analysis of foreign trade data at the SITC fou.